PENGARUH METODE PEMBELAJARAN COURSE REVIEW HORAY BERBANTU PERMAINAN PUZZLE TERHADAP HASIL BELAJAR TEMATIK SISWA KELAS IV SD NEGERI BENDUNGAN SEMARANG - Leviatun Khasanah; Qoriati Mushafanah; Muhajir Muhajir. (Universitas Syiah Kuala, 2018)
This research was motivated by the low learning outcomes thematic fourth grade students of SD Negeri Bendungan Semarang. This is due to the lack of creativity of teachers in active learning methods, creative, innovative, and fun. The problem of this research is there any influence teaching methods Course Review Horay assisted Puzzle game on learning outcomes thematic my goal Scene 6 Subtheme 2 Amazingly my ideals fourth grade students of SD Negeri Bendungan Semarang ?. Goals to be achieved in this research is to determine the effect of teaching methods Course Review Horay assisted Puzzle game on learning outcomes thematic Cita-citaku Scene 6 Subtheme 2 Hebatnya Cita-citaku fourth grade students of SD Negeri Bendungan Semarang . This study uses a quantitative method Pre-Experimental Design with the form of One-group pretest-posttest Design Subjects in this study were all fourth grade students of SD Negeri Bendungan Semarang 2017/2018 school year numbered 36 students. The data in this study were obtained through testing. The results of this study states that the average value posttest (82) has increased from an average pretest score (58). Thus an increase in thematic learning outcomes of students with learning methods Course Review Horay assisted Puzzle.Hasil game hypothesis on the cognitive aspects of student learning outcomes showed that t_count t_table, that is 12,487 2,030 so Ha is received so that it can be concluded that the teaching methods Course Review Horay assisted Puzzle game affects the outcome of the thematic study of fourth grade students of SD Negeri Bendungan Semarang.